Uji aktivitas antibakteri ekstrak jerami bawang merah dengan pelarut metanol terhadap bakteri Escherichia Coli secara In Vitro - Prayitno, Ryantoko Setyo; Suharyono, Eko (JURNAL BIOLOGICA SAMUDRA, 2024)
The development of livestock businesses is often hampered by diseases caused by bacteria, one of which is the Escherichia Coli bacteria. One of the compounds that can ward off bacteria is flavonoids. One of the plants that contain flavonoids is shallots. The flavonoids in shallots are able to kill bacteria by denaturing bacterial cell proteins and lysing the cytoplasmic membrane. It is alleged that waste from shallots, namely shallot straw, also has potential as a natural antioxidant and antibacterial. This aims to determine the antibacterial activity of shallot straw extract with methanol solvent on Escherichia Coli bacteria. The research used two stages, the first stage was extracting shallot straw using methanol solution, the next stage was testing antibacterial activity using the disc diffusion method. The study used a completely randomized design with different concentrations of shallot straw extract (10%, 20%, and 30%). Optimum conditions to inhibit E Coli bacteria are at a concentration of 30% with an inhibition zone of 12.82 mm